Swaziland : Selected Development Impact of HIV/AIDS - World Bank (Washington, DC, 2013)
This report was initiated as an exercise to assist policy makers in Swaziland in their effort to incorporate HIV/AIDS into the planning process on a regular basis, and provides an overview of selected, likely development impacts of the epidemic for the country. Through conventional demographic, and economic models, it analyzes the HIV/AIDS impacts on the economy, and illustrates how these impacts can be incorporated in the regular planning processes - including annual budgeting - in the finance, and development ministries of Government. It also points at the need for monitoring the progression of the epidemic, through further research, and improvements in existing instruments. Chapter I reviews the status of HIV/AIDS, and the factors exacerbating the spread of the epidemic, and Chapter II examines the demographic impact, and its effect on labor, and human resource development, for unlike population control programs, AIDS epidemic damages the economy by reducing the size of the economically active population, and imposes a "shock" on the socioeconomic status of the household. Chapter III analyzes the impact of the disease on the public service, and Chapter IV reviews policy options. Recommendations suggest reducing HIV transmission, and AIDS morbidity, and, proposes initiating programs for skills replacement to mitigate the negative economic impact of AIDS, outlining key areas of preventive action.